Bio-Oil Production from Multi-Waste Biomass Co-Pyrolysis Using Analytical Py–GC/MS - Sabah Mariyam (14150859) (2022)
Background Bioenergy attracts much attention due to the global demand for renewable and sustainable energy resources. Waste biomass feedstocks—date pits, coffee waste, and cow dung—require efficient and environmentally friendly waste-management technologies such as pyrolysis. Fast pyrolysis occurs at fast heating rates (10–100 °C/s), generates high bio-oil yields, and is the most widely used process for biofuel generation. The aim of the study is to compare the effect of pyrolysis between single, binary, and ternary feeds on thermal degradation behavior and bio-oil composition. Methods Thermogravimetric analysis (TGA) was conducted at 30 °C/min from room temperature to 850 °C to understand the thermal degradation behavior of the biomasses. A Pyroprobe® reactor—a micro-scale pyrolyzer—was used to conduct the fast pyrolysis at 500 °C with a heating rate of 10 °C/s, and the volatile contents were quantified using a gas chromatograph–mass spectrometer (GC/MS). Results The (TGA) showed three main stages of decomposition following dehydration, devolatilization, and char degradation for the different single and multiple feeds. According to the identified compounds, the bio-oil components are broadly identified as aldehydes, amines, aliphatic, aromatics, alcohols, furans, ketones, and acids. The three single-biomass pyrolysis products have four compounds in common, acetic acid and ketone groups (acetic acid, 2-propanone, 1-hydroxy-, benzyl methyl ketone, and 1,2-cyclopentanedione). Conclusion The bio-oil generated from the feeds comprises great potential for volatiles, diesel, and gasoline production with carbon atoms ranging from C2–C33. Future studies should focus on understanding the effect of procedural parameters, including blending ratio, temperature, and heating rates, on bio-oil composition. Additional molecular techniques should be employed to understand biomass components’ reaction mechanisms to produce useful bio-oil products. Other Information Published in: Energies License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/en15197409